To share or not to share: A social-cognitive internalization model to explain how age discrimination impairs older employees' knowledge sharing with younger colleagues. Issue 1 (2nd January 2021) - Fasbender, Ulrike; Gerpott, Fabiola H.
ABSTRACT: Older employees' knowledge sharing with younger colleagues is pivotal for organizational knowledge retention. We developed a social-cognitive internalization model that explains why older employees' knowledge sharing with younger colleagues is often inhibited. Specifically, we focused on perceived age discrimination at work as a threat to older employees' perceptions of their job-related capabilities (i.e., occupational self-efficacy), which in turn reduces older employees' knowledge sharing with younger colleagues. Study 1, a field study with 100 age-diverse employee dyads provided support for our framework. Older employees who perceived age discrimination showed lower occupational self-efficacy, which predicted less knowledge sharing with younger colleagues. To help organizations address this challenge, we extended our theorizing by considering organizational context and hypothesized supportive effects of the availability of age-specific HR practices (i.e., HR development and HR accommodation activities). We replicated the first study's findings in Study 2 using a three-wave survey with 472 older employees. Additionally, we found that HR accommodation practices strengthened the positive relation between occupational self-efficacy and knowledge sharing. Hence, HR accommodation practices constitute a double-edged sword: They helped older employees with higher occupational self-efficacy but impair knowledge sharing by older employees with lower occupational self-efficacy resulting from perceived age discrimination.